Karakteristik Tempat Penampungan Air Positif Larva Aedes, Vektor Demam Berdarah: Studi Literatur - CATARINA LILIAN CHRISTINE; FIRDA AULIA WIRAPUTR; ARINI LILLAH WIRAPUTRI; HEBERT ADRIANTO (Hang Tuah Medical Journal, 2024)
Background: The Aedes aegypti mosquito is a vector of many diseases that transmit diseases such as yellow fever, filariasis, chikungunya, zika, and Dengue Haemorrhagic Fever (DHF). The eradication of DBD mosquito is carried out mainly in places that have potential to become mosquito habitats, like containers or water reservoirs. Community action against the eradication of mosquito nests (PSN) rated 3M PLUS is still less, especially in draining the bathtub regularly. This paper aims to collect information on the characteristics of the container and its effect on the presence of aedes aegypti mosquito larvae so that a model of a mosquito larva-free bathtub can be created based on the morphometric study.Method: This paper is a narrative review of literature that analysed 21 research journals from 2015 to 2019, consisting of 17 Indonesian journals, four English journals, two books, and four articles Indonesian Ministry of Health. Result: The study found bathtubs that aren’t at risk as breeding places for larvae, are made of cement, are textured, brightly coloured, such as yellow, orange, or light green, have a cover, volume less than 50 litres, and a height of 80 cm.Conclusion: Bathtub’s becomes the most potential breeding place for Aedes aegypti. Based on the literature study, the characteristics of the bathtub can influence the presence of mosquito larvae, so to achieve a larvae-free bathtub, the bathtub can be modified according to the characteristics that have already been found.